PENGARUH LOCUS OF CONTROL DAN MOTIVASI TERHADAP KINERJA GURU DENGAN MEDIASI KEPUASAN KERJA (Studi Pada SMPN 2 dan SMPN 3 Wonokerto Pekalongan) - Sakhori, 12.52.02.0040; Susilowati, Yeye (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to examine and analyze " the influence of locus of control and motivation on teacher performance with mediation of job satisfaction ( study on SMP and SMP 2 3 Wonokerto pekalongan ) ". The population in this study is 45 respondents , the sampling method used in this study sesus . Testing in this research that uses, Test instrument with, Classical Assumption Test 3 ) Test Test model used is R2 ( coefficient of determination ) , F Test ( Goodness of Fit ) and t test ( t - test) . Hypothesis Testing in this study used regression analysis . Hypothesis testing is used in significance level ( Î± ) of 5% and testing mediation effects. Based on the results of the study can be summarized as follows: the locus of control has a positive and significant impact on job satisfaction, motivation has a significant positive effect on job satisfaction, the locus of control has a positive and significant impact on teacher performance, motivation has a positive influence significant impact on teacher performance, job satisfaction has a significant positive effect on teacher performance. Keywords : Locus Of Control , Motivation , Job Satisfaction , Performance